Relations of multivariate goal profiles to motivation, epistemic beliefs and achievement. (1st February 2019) - Zhou, Mingming; Adesope, Olusola O.; Winne, Philip H.; Nesbit, John C.
Abstract: We examined whether undergraduates' achievement goal orientations could be represented as profiles and whether profiles were linked to self-reported motivation, epistemic beliefs and academic achievement. Data collected during an undergraduate course were analyzed using a clustering technique. Using the 2 × 2 goal model (Elliot & McGregor, 2001 ), we identified five achievement goal profiles. Our findings suggest the interaction of goal orientations supports varying interpretations of students' motivation and learning beliefs. Although no statistically significant differences in achievement were found across clusters, a High-Approach-Low-Avoidance cluster displayed an adaptive profile that was most positive towards learning and self but least anxious about exams. In contrast, a Performance-Avoidance-Dominant cluster demonstrated a maladaptive pattern of lowest self-efficacy and task value, and higher anxiety. Further, High-Approach-Low-Avoidance and Low-Performance-Avoidance clusters recognized that knowledge is not simple and authority could be questioned, compared to the other groups.